Reconfiguring the Nation through Song: Struggles over National Imaginaries in the Chilean Nueva Canción and the Argentine Nuevo Cancionero (Revista Argentina de Musicología, 2026)
This article examines, from a comparative perspective between Chile and Argentina, the crisis and reconfiguration of the national imaginaries articulated around folk-based song from the late 1950s to the early 1970s. It explores how certain paradigms became established as legitimate representations of the nation through selective processes that privileged particular territories and musical repertoires over others. Against these essentialist imaginaries, the article investigates the conditions that enabled the emergence of the Chilean Nueva Canción and the Argentine Nuevo Cancionero, two movements associated with the so-called political song. In Chile, the consolidation of the huaso imaginary as the dominant matrix of national identity was challenged by the Nueva Canción movement, which expanded the country's sonic landscape, gave visibility to subaltern social actors, and promoted a broader Latin American perspective. In Argentina, the decline of the criollista imaginary created space for the Nuevo Cancionero, which introduced new symbolic references and territorial imaginaries, although without fully establishing a cultural counter-hegemony. In both cases, the political song movements of the 1960s and 1970s became privileged sites for re-signifying tradition and reshaping national imaginaries, not by rejecting inherited cultural frameworks but by transforming their meanings.Editorial History:Received: March 24, 2026Accepted: May 29, 2026
Keywords: political song; national imaginaries; Argentine Nuevo Cancionero; New Chilean Song